Blockchain and Financial Markets: General Features of the Regulatory Impact of the Application of Blockchain Technology in the Credit Markets of Latin America - Corredor Higuera, Jorge Armando (2018)
The purpose of this document is to analyze, based on technological criteria, regulatory standards and international recommendations, the impact of blockchain technology on credit markets and how such dynamics could have direct effects on Latin American markets, i.e., producing greater efficiency and financial inclusion in the region. For this purpose, the scope of blockchain technology will be contextualized, the possible applications of said technology in the financial markets will be developed, and finally the regulatory proposals on the application of said technology in the Latin American credit markets will be analyzed in relation to risk management and financial inclusion.